Surgical resection of splenic metastasis from the adenosquamous gallbladder carcinoma: A case report. (2016) - Utsumi, Masashi; Aoki, Hideki; Kunitomo, Tomoyoshi; Mushiake, Yutaka; Kanaya, Nobuhiko; Yasuhara, Isao; Arata, Takashi; Katsuda, Kou; Tanakaya, Kohji; Takeuchi, Hitoshi
Highlights: We report a case of splenic metastasis of adenosquamous carcinoma of gallbladder. Splenic metastasis of adenosquamous gallbladder carcinoma is a rare. Resection of splenic metastasis may represent the treatment for prolonging survival. Abstract: Introduction: Splenic metastasis of gallbladder carcinoma is extremely rare. Specific anatomical, histological, and functional properties of spleen are believed to be responsible for the rarity of solitary splenic metastasis. Presentation of case: We present the case of a 62-year-old female who developed metachronous splenic metastasis of adenosquamous carcinoma of the gallbladder. We performed central bisegmentectomy of the liver for gallbladder carcinoma. The patient subsequently presented 3 months later with isolated splenic metastasis and liver metastasis. Splenectomy and partial hepatectomy was performed at this time. Histological examination confirmed metastatic adenosquamous carcinoma of the gallbladder. No signs of recurrence were observed at 3 months after the second surgery. Discussion: Although splenectomy provides a potential means of radical treatment in patients with isolated splenic metastases, it should be performed with caution as splenic metastatic lesions may represent the initial clinical manifestation of systemic metastases at multiple sites. In this case, radical surgery was performed following the confirmation of no new unresectable metastatic lesions or systemic dissemination. Conclusion: This is the first report on the adenosquamous splenic metastasis from the gallbladder carcinoma. Curative resection may be the treatment of choice for prolonging survival in patients with the splenic metastasis of gallbladder carcinoma.